FOREIGN EXPERIENCE FOR PROVIDING THE STATE ECONOMIC SECURITY - Hbur Zoryana Volodymyrivna (World Science, 2018)
The article deals with approaches to interpretation of the economic security concept. The main functions of economic security have been characterized, they are divided into five groups: protective, regulatory, preventive, innovative and social. System of the state economy security represented by internal and external subsystems, which have its components, is analyzed. The main elements of external security subsystem are determined as technological, commercial and financial elements. The subsystem of internal security includes the industrial, technical, raw material, energy, ecological, and information components. Accordingly, internal and external threats to the state economic security are identified; they specify the insufficient level of economic stability, and as a consequence, reduction of the economic security level for each state. The main approaches to ensuring economic security in European countries have been considered, as well as analysis of global economic competitiveness dynamics index in European countries in 2016-2017.